Students' Perceptions of The Application of Recitation Methods During the Covid-19 Pandemic - Muhammad Fadli; Mazrur Mazrur; Surawan Surawan (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
This study aims to find out 1) the perceptions of students of the PAI study program class of 2019 FTIK IAIN Palangka Raya on the application of the Recitation Method during the covid-19 pandemic, and 2) the impact of the application of the Recitation Method during the covid-19 pandemic on students of the 2019 FTIK PAI study program. IAIN Palangka Raya. The type of research used in this study is mixed methods research. The subjects are 161 students of the 2019 Islamic Islamic Education study program FTIK IAIN Palangka Raya and the PAI Homebase lecturer who teaches at the 2019 Islamic State Islamic Studies study program FTIK IAIN Palangka Raya as informants. Data collection techniques using questionnaires, interviews, and documentation, data validation techniques using source triangulation and tabulation percentages, and data analysis techniques using data reduction, presentation, and verification. The results of this study indicate that: 1) PAI students' perceptions of the class of 2019 on the application of the Recitation Method during the Covid-19 pandemic on the cognitive component were in the excellent category with a percentage of 67.1%, the perception of PAI students for the class of 2019 on the affective part was in the perfect type with a percentage 52.2%, the perception of PAI students for the class of 2019 on the conative element is in the ideal variety with a percentage of 69.6% with an average rate of the overall cognitive, affective, and conative components as much as 62.97%. So, it can be said that the perception of PAI students from the class of 2019 on the application of the Recitation Method during the Covid-19 pandemic was in the excellent category as a whole. This can be seen from the responses of students who accept the application of the Recitation Method positively despite various obstacles; PAI students of the 2019 batch still try to do their assignments seriously and as much as possible. 2) As for the impact of the implementation of the Recitation Method during the covid-19 pandemic on students PAI study program batch 2019 FTIK IAIN Palangka Raya consists of positive impacts, namely a) helping to understand the material, b) honing knowledge and skills, c) fostering positive habits, and the negative impact of applying the Recitation Method during the covid-19 pandemic on PAI study program students’ class of 2019 are a) interaction barriers and b) facility constraints.